Expressão da Miostatina e ActRIIB em ratos submetidos a dieta hiperlipídica e exercício - Bueno, Patricia de Godoy (2009)
Myostatin (MSTN) is a secreted growth factor expressed in skeletal muscle and negatively regulates skeletal muscle mass. MSTN is also expressed in adipose tissue. Recent data suggest that MSTN regulates adipogenesis and energy metabolism. Aims: The objective of this study was to determine the influence of exercise in the expression of myostatin (MSTN) and its receptor in fat and muscle in obese and insulin resistant rats. Methods: Adult male Wistar rats were housed under controlled conditions (20-220 C, 10-14h light-dark cycle) and were allowed free access to standard rodent chow (control group, CG) or HF diet (58% Kcal from fat, high-fat group, HG) during 12 weeks. Glucose tolerance test (GTT) and insulin tolerance test (ITT) were performed before and at 3, 4, 8 and 12 weeks after diet regimen. After 12 weeks, CG and HG rats were randomly assigned to a swimming training group (CGE and HGE) or a sedentary group (CGS and HGS). CGE and HE swam individually in water tanks (50x30cm) at 340 C, for 45 minutes at 0900h and 1700h, 5 day week-1, for 4 weeks. After this period, rats were submitted again to GTT and ITT and then killed by decapitation. GTT area under the curve was lower in HE compared to HGS. White gastrocnemius muscle and fat pads were dissected, weighted, immediately cooled in liquid nitrogen and stored at - 700 C for subsequent analysis. The mRNA levels were quantified by real time RT-PCR. The animals were maintained according to the local University Committee guidelines for the care and use of laboratory animals. Results: HG developed insulin resistance according to GTT and ITT tests. Adipose fat pads (epididymal, retropritoneal and mesenteric) were 2 to 3 times heavier in high-fat fed groups (HGS and HGE) compared to standard chow fed groups (CGS and CGE). In HGS, the expression of MSTN was significantly higher in mesenteric fat and lower in epididymal fat and Brown tissue adipose (BAT) compared to CGS rats. The expression of ActRIIB significantly decreased in epididymal fat and BAT. The training resulted in decreased of expression of expression of MSTN in muscle and mesenteric fat and increased expression in BAT of CGE compared CGS. The expression of ActRIIB increased significantly in mesenteric fat and BAT in CGE compared to CGS. The expression of MSTN decreased in mesenteric fat and increased in epididymal fat and BAT in HGE compared to HGS. The expression of ActRIIB decreased in muscle and mesenteric fat and increased in BAT in HGE compared to HGS. Conclusions: These data suggest that the expression of MSTN in fat tissues may be involved in the metabolic response of rats submitted to high fat diet and exercise.